A Chinese patient with POLR3A-related leukodystrophy: a case report and literature review - Sun, Lei; Lin, Weihong; Meng, Hongmei; Zhang, Wuqiong; Hou, Shuai (Frontiers in Neurology, 2023)
Background: Leukodystrophies are hereditary white matter diseases characterized by genetic polymorphisms and considerable phenotypic variability. They can be classified into myelin and non-myelin malformations. These diseases are rare, affecting 1 out of 250,000-500,000 individuals and can manifest at any age. A subtype of leukodystrophy, associated with missense mutations in the RNA polymerase subunit III (POLR3A) gene, is inherited in an autosomal recessive manner.Case Report: We report and analyse a case of a 34-year-old female who presented with ataxia.Magnetic Resonance Imaging (MRI) of the brain revealed demyelinating lesions in the white matter.Genetic testing identified the c.4044C>G and c.1186-2A>G variants in the POLR3A gene. The patient was diagnosed with hypomyelinating leukodystrophy type 7 and received neurotrophic and symptomatic supportive therapy. However, after one month of follow-up, there was no improvement in her symptoms.POLR3A-induced leukodystrophy is relatively rare and not well understood, making it challenging to diagnose and easy to overlook. The prognosis for this disease is generally poor, significantly impacting the quality of life of affected individuals. Currently, no cure is available for this condition, and treatment is limited to managing symptoms. Further research into new treatment methods for POLR3A-induced leukodystrophy is imperative to improve the quality of life and potentially extend the life expectancy of patients.